(untitled) (Filološke pripombe, 2019)
In this article semantics of Russian and Czech languages’ lexis ascending to the ancient root *PaRS is compared. The fulfilled study has revealed that the lexical meanings of the analyzed Russian and Czech words of this root are rather similar, but at the same time the destiny of these words occasionally differs: for example, the words of this root in the meaning ‘dust’ are disappearing from Russian literary lexis whereas it remains still essential in the Czech one.